PENGGUNAAN RAGAM PERMAINAN KINESTETIK SEBAGAI UPAYA PENINGKATAN KETERAMPILAN GERAK DASAR SDN SAWUNGGALING VIII/389 SURABAYA - Aristono, Toton; Tuasikal, Abdul Rachman Syam; Moedajanah, Moedajanah (Jurnal Muassis Pendidikan Dasar, 2023)
This research was conducted due tothe observaion result of class II students SDN Sawunggaling VIII/389 Surabaya that there are still many students who have difficulty practicing basic movement skills. Based on the observation, there are still many students who get an assessment under the Minimum Completeness Criteria (KKM). This study aimed to determine the increase in basic movement skills of SDN Sawunggaling VIII/389 Surabaya students through the use of a variety of kinesthetic games. The method chosen in this research was classroom action research with two cycles. The research subjects were all students of class II, totaling 27 students, with 12 male students and 15 female students. The research was carried out in four stages including planning, implementing, observing, and reflecting. Data obtained from the results of observations and tests. The data analysis technique used descriptive data analysis techniques with percentages. The results showed that the first cycle of classical completeness reached 63% and the second cycle of classical completeness reached 85%. Based on these results, it can be said that the classical value was achieved in cycle II. Moreover, the results of this study could be concluded that the use of a variety of kinesthetic games can improve the basic movement skills of SDN Sawunggaling VIII/389 Surabaya students.